PERLINDUNGAN HUKUM TERHADAP PASIEN KORBAN MALPRAKTEK MEDIS DALAM PERSPEKTIF HUKUM PERDATA - Christanto, Eunike Aryaningrum; Yuyut Prayuti, Yuyut Prayuti; Arman Lany, Arman Lany (Program Studi Magister Ilmu Hukum Universitas Islam Nusantara, 2024)
This study aims to determine the responsibility of health services or hospitals to patients who are victims of medical malpractice, legal protection for patients as consumers of services in the field of medical services, and legal protection for patients as consumers of services in the field of medical services. The type of research used in this paper is normative legal research or library research. The approach method used in this research is the statutory approach. Secondary research sources used include primary legal materials and tertiary legal materials. Based on the results of the study, it can be concluded that 1) The form of regulation of medical personnel who commit malpractice is regulated in Article 19 paragraph (1) of Law no. 8 of 1999 concerning Consumer Protection and in Article 58 paragraph (1) of Law no. 36 of 2009 concerning Health which discusses compensation for a person, health worker and or health provider who causes losses due to errors or omissions in health services; 2) The form of deviation from the agreement between a doctor and a patient that can harm the patient is a breach of contract or an unlawful act committed by a doctor. The losses suffered by the patient can be in the form of material or immaterial losses; and 3) Civil liability for medical personnel must be from unlawful acts (onrechtmatige daad) in accordance with the provisions of Article 1365 of the Civil Code and the responsibility of hospitals related to vicarious liability under the provisions of Article 1367 of the Civil Code.